Pengaruh Electronic Word Of Mouth (E-WOM) Terhadap Keputusan Pembelian Pada Marketplace Tokopedia (Studi Pada Mahasiswa Pendidikan Ekonomi IKIP PGRI Bojonegoro) - Al Fina Aini Rohmaha; Ayis Crusma Fradani; Ari Indriani (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
Electronic Word Of Mouth (E-WOM) is a very important place for consumers to give their opinions and is considered more effective than WoM because of it’s accessibility and wider reach. From this increase, researchers took the initiative to conduct this research with the aim of knowing the effect of Electronic Word Of Mouth (E-WOM) on product purchasing decisions on the Tokopedia marketplace. The number of samples taken was 70 respondents using a non-probability sampling technique, namely purposive sampling technique. Data collection techniques were carried out by distributing online questionnaires with google forms and analyzed by simple linier regression. The result showed that there was an influence between Electronic Word Of Mouth (E-WOM) on purchasing decisions, with the test results in this study obtained tcount > ttable (3,446 > 1995) with a significance < 0,005. This means that H0 is rejected and H1 is accepted, thus Electronic Word Of Mouth (E-WOM) has a significant positive effect on the involvement of purcashing decisions. Keywords: Electronic Word Of Mouth (E-WOM), Marketing, Social Media, Tokopedia, Purchase Decisions